Prevalence of Cytomegalovirus Infection among Suspected Infants in Baghdad - Tareef Fadhil Raham (مجله كليه طب الكندي, 2022)
Background: Cytomegalovirus (CMV) virus is a recognized important cause of congenital CMV infection which carries a significant risk for symptomatic disease and developmental defects in newborns. Its prevalence varies from place to other and time to time. This study is conducted to estimate its prevalence in Baghdad among infants suspected of having a congenital infection and to study the associated findings.